The Urgency of STEM Education in Indonesia - Nugroho, Oktian Fajar; Permanasari, Anna; Firman, Harry; Riandi, Riandi (Jurnal Penelitian dan Pembelajaran IPA, 2021)
Industry 4.0 and 21st-century skills are quickly increasing and becoming more knowledgeable. In this century, the primary purpose of our educational system should be to prepare students to live in the world. STEM Education has garnered increasing attention in recent years, and it is important to comprehend STEM Education. Indonesia is one of the largest countries in Southeast Asia with a vast number of human resources that need to be developed. The purpose of this study was to investigate the urgency of STEM education in Indonesia within the scope of 21st-century skill categories using the content analysis method, to investigate best practices of STEM education for teachers by investigating engineering design skills training, and to review the literature from 1990 to 2016 that has focused on the development of STEM education around the world. The data demonstrated that STEM Education has grown over the world and has a significant influence on students' idea comprehension, literacy, and creativity. Many studies show that the best strategy for science teachers is to incorporate STEM education. STEM is relevant to everyday life and improve student performance. These findings are important to be implemented in Indonesia for STEM Education implementation in Indonesia